Boron Ester‐Catalyzed Amidation of Carboxylic Acids with Amines: Mechanistic Rationale by Computational Study. Issue 18 (8th August 2018) - Jiang, Yuan‐Ye; Hu, Ben; Xu, Zhong‐Yan; Zhang, Rui‐Xue; Liu, Tian‐Tian; Bi, Siwei
Abstract: A novel boron ester‐catalyzed amidation reaction of carboxylic acids and amines with unprecedented functional group tolerance was recently reported. To gain deeper insights into this reaction, a computational study with density functional theory methods was performed in this manuscript. Calculations indicate that the amidation starts with the condensation of carboxylic acids with the boron ester catalyst. The resulting monoacyloxylated boron species further undergoes the carboxylic acid‐assisted nucleophilic addition with amines to generate the amide product and a monohydroxyboron species. The condensation of the carboxylic acid with the monohydroxyboron species with the assistance of an amine regenerates monoacyloxylated boron species to finish the catalytic cycle. The rate‐determining step is catalyst regeneration and the amine‐coordinated monohydroxyboron species is the resting state in the catalytic cycle. The present results are consistent with the previous NMR study and the observed reaction orders of catalyst and substrates; it is expected to benefit further reaction optimization. Abstract : Mechanistic rationale : The mechanism of boron ester‐catalyzed amidation of carboxylic acids and amines was studied by DFT calculations, which elucidated the resting states of catalysts and substrates, the rate‐determining steps, and the self‐catalytic role of carboxylic acids. The results are consistent with the previous NMR study and observed reaction orders of catalysts and substrates.